(untitled) (Journal of Universal Science Research, 2023)
In this article, the transformation of settlements in the form of the first city located in the south of Central Asia, the culture of the first city, in the process of commenting on the concept of "first city" or "city" is analyzed methodologically and scientifically based on a comparative analysis.